Kultur Pakan Alami Cacing Sutra (Tubifex Sp.) Dan Pemberian Pakan Larva Ikan Lele (Clarias Sp.) Di Desa Fadoro Dusun Bawosalo’o, Kec. Mandrehe, Kab. Nias Barat - Gea, Angel Sri Ayu; Estin Krisdila Zebua; Agnes Juwita Dawolo; Heppi Kristiani Waruwu; Irfan Waruwu; Martin Gulo; Ratna Dewi Zebua (Jurnal Perikanan dan Kelautan, 2025)
This study explores the culture of tubifex worms (Tubifex sp.) as natural feed to enhance the growth of catfish larvae (Clarias sp.). Tubifex worms are known for their high nutritional content, with protein levels reaching 55-66%, crucial for larval growth. The culture activity was conducted in Bawosalo’o, Nias Barat, from May 2 to May 31, 2025. Observations showed an increase in larval length from 0.72 cm on the first day to 1.1 cm by the seventh day, with a survival rate of 60%. Water quality, including temperature and pH, was well-maintained, supporting larval survival. Additionally, using tubifex worms as natural feed not only improved growth but also contributed to sustainable and environmentally friendly aquaculture practices. This research concludes that tubifex culture is an effective method for catfish larvae cultivation and recommends enhancing knowledge of breeding techniques and water quality management.